2021
DOI: 10.1111/jmg.12637
|View full text |Cite
|
Sign up to set email alerts
|

Petrochronology of high‐pressure granulite facies rocks from Southern Brasília Orogen, SE Brazil: Combining quantitative compositional mapping, single‐element thermometry and geochronology

Abstract: We use a combination of several in situ techniques to assess the P‐T‐t path of high‐pressure granulites from the Passos Nappe in the Southern Brasília Orogen (SE Brazil). Quantitative element mapping and single‐element thermometers (Zr‐in‐rutile and Ti‐in‐quartz) are coupled with P‐T pseudosections and monazite and rutile dating. Compositional and temperature maps, based on cathodoluminescence mapping and in situ analyses of Ti‐in‐quartz, are presented as a novel approach to evaluate crystallization temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 101 publications
(188 reference statements)
0
3
0
1
Order By: Relevance
“…These concentrations are equivalent to the temperatures of ~700°C for the Ti‐in‐zircon thermometry (Ferry & Watson, 2007) and ~ 420°C for the Ti‐in‐quartz thermometry (at 5 kbar; Thomas et al, 2010). Recent studies have shown that the results of Ti‐in‐zircon (e.g., 550–1070°C; Fu et al, 2008; Watson et al, 2006; Yuguchi et al, 2016) and Ti‐in‐quartz (e.g., 300–1000°C; Ashley & Law, 2015; Fumes et al, 2021; Kendrick & Indares, 2018; Spear & Wark, 2009; Storm & Spear, 2009; Wark & Watson, 2006) thermometers were successfully applied to evaluate crystallization conditions of most igneous rocks and equilibrium conditions of medium‐ to high‐grade metamorphic rocks. The calculated temperature conditions in this study indicate that the Ti‐in quartz protocol can be used to evaluate the recrystallization of quartz down to greenschist facies conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concentrations are equivalent to the temperatures of ~700°C for the Ti‐in‐zircon thermometry (Ferry & Watson, 2007) and ~ 420°C for the Ti‐in‐quartz thermometry (at 5 kbar; Thomas et al, 2010). Recent studies have shown that the results of Ti‐in‐zircon (e.g., 550–1070°C; Fu et al, 2008; Watson et al, 2006; Yuguchi et al, 2016) and Ti‐in‐quartz (e.g., 300–1000°C; Ashley & Law, 2015; Fumes et al, 2021; Kendrick & Indares, 2018; Spear & Wark, 2009; Storm & Spear, 2009; Wark & Watson, 2006) thermometers were successfully applied to evaluate crystallization conditions of most igneous rocks and equilibrium conditions of medium‐ to high‐grade metamorphic rocks. The calculated temperature conditions in this study indicate that the Ti‐in quartz protocol can be used to evaluate the recrystallization of quartz down to greenschist facies conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Batanova et al, 2018) and are helpful in achieving low detection limits (<6 ppm), even under extreme analytical conditions (e.g., 20–25 kV accelerating voltage, 200–900 nA beam current, 180–960 s counting time; Batanova et al, 2018; Donovan et al, 2011). Several authors have applied these improved strategies to measure trace element concentrations from monazite (Deshmukh et al, 2017; Hrushikesh et al, 2020 and the references therein; Jercinovic & Williams, 2005; Jercinovic et al, 2012; Prabhakar, 2013), quartz (Donovan et al, 2011; Fumes et al, 2021; Kendrick & Indares, 2018; Rusk et al, 2006; Wark & Watson, 2006) and olivine (Batanova et al, 2015; Batanova et al, 2018; Shaikh et al, 2017; Sobolev et al, 2005; Sobolev et al, 2007; Sobolev et al, 2009). In this study, we have adopted some of these advancements in acquiring statistically improved Ti analysis using EPMA.…”
Section: Methodsmentioning
confidence: 99%
“…As unidades da NP compreendem uma sequência plataformal depositada na margem oeste do Cráton São Francisco (Zanardo, 1992;Simões, 1995). Essa sequência apresenta gradiente metamórfico invertido onde, em direção ao topo, ocorrem as rochas de mais alto grau, como granulitos de alta pressão e eclogito retrogradado (Simões, 1995;Luvizotto, 2003;Luvizotto et al, 2011Luvizotto et al, , 20122014;Santos et al, 2021;Fumes et al, 2022;Simões et al, 2022).…”
Section: Introductionunclassified
“…Such rates can be constrained by combining geothermobarometric and geochronological methods (e.g. Fumes et al, 2022; Morita et al, 2022; Tajčmanová et al, 2006; Zou et al, 2021). Simulation of cation diffusion in garnet is another method that can provide key constraints on the timescales of metamorphic processes (e.g.…”
Section: Introductionmentioning
confidence: 99%